INTEGRATED TEACHER EDUCATION PROGRAMME: BENEFITS AND CHALLENGES - Bhattacharya, Vani; Puri, Jyoti (International Journal of Research -GRANTHAALAYAH, 2025)
With the aim of improving the quality of education and making teacher education more professional and holistic, the Government of India has envisaged the Integrated Teacher Education Programme (ITEP) under the National Education Policy 2020. This programme is a four-year graduate level course, in which subject knowledge and teacher training are presented in an integrated manner. ITEP is more coherent, modern and teaching-oriented as compared to the traditional B.Ed. course. This research paper highlights the major benefits of ITEP, which include time saving, high quality training, inclusive approach and multidisciplinary development. Since this course starts directly after class XII, it provides students with an opportunity to become teachers quickly. Also, it incorporates various subjects like arts, science, humanities and education, which makes it possible to develop multidimensional competence of teachers. However, many challenges are also faced in implementing ITEP. The major problems include shortage of qualified and trained teachers, inadequacy of institutional resources and lack of professional maturity among students at an early stage. To address these challenges, there is a need for concerted policy efforts, special training for teachers, and equipping institutions with necessary educational and physical resources. This study provides important insights to policymakers, teacher training institutions and researchers in understanding the effectiveness, feasibility and possibilities of improvement of ITEP.